2001
DOI: 10.1007/s002770000268
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular large B-cell lymphoma or intravascular lymphomatosis: report of a case diagnosed by testicle biopsy

Abstract: Intravascular large B-cell lymphoma or intravascular lymphomatosis (IVL) is an extremely rare form of non-Hodgkin's lymphoma. The most common clinical sign is fever of unknown origin (FUO). Histologically, there is proliferation of malignant lymphoid cells within vascular lumina. Cytologically, the cells have features similar to those found in classical large cell lymphoma. Examination of pulmonary artery blood showed the presence of this abnormal population in our patient; to the best of our knowledge there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Diagnosis is made mostly by biopsy of the skin or brain, but IVL has been reported after biopsy of the prostate, kidney, gallbladder, testis, lung [15,16], and bone marrow as in our case [17]. In most of the reported cases, malignant lymphocytes usually show B-cell lineage, and T lymphocyte IVL is rare [18].…”
Section: Discussionmentioning
confidence: 98%
“…Diagnosis is made mostly by biopsy of the skin or brain, but IVL has been reported after biopsy of the prostate, kidney, gallbladder, testis, lung [15,16], and bone marrow as in our case [17]. In most of the reported cases, malignant lymphocytes usually show B-cell lineage, and T lymphocyte IVL is rare [18].…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that about 15% of IVL patients have had a previous or concomitant malignancy with NHL being the most commonly associated hematopoietic malignancy [6]. Clinical features are heterogeneous and frequently include B symptoms, fever of unknown origin, and poor performance status [6][7][8][9][10][11]. Edema, however, has been reported only as a rare associated symptom at the time of presentation [8].…”
Section: Commentarymentioning
confidence: 99%
“…Laboratory abnormalities frequently include anemia, an elevated LDH and an elevated ESR [6][7][8][9]. Diffuse organ involvement has been documented with cutaneous and CNS manifestations being most prevalent [6][7][8][9][10][11][12]. A common feature of this disease, however, is the surprising degree of sparing of the surrounding tissue and absence of lymphoma cells in the lymph nodes and reticuloendothelial system [6][7][8][9].…”
Section: Commentarymentioning
confidence: 99%
“…Diagnosis is typically by biopsy of the skin or brain or bone marrow(5, 6) or other lesion in certain variant cases (7,8) including the adrenal grands (9), although occasional worsening has been described after brain or spinal cord biopsy (10). Skin lesions of IVL include teleangiectasias, hemorrhagic nodules and leg lymphedema(3).…”
Section: Skin Biopsymentioning
confidence: 99%
“…Such poor prognosis reflects in part delays in diagnosis. Amongthese therapies, patients treated by a combination of chemotherapy were reported to have long-term survival and to be alive in complete remission (4,(6)(7)(8)(9)(10)13). It is the most favorable therapy at present.…”
Section: Skin Biopsymentioning
confidence: 99%